Cytogenetic studies of four South American species of Paullinia L. (Sapindaceae) - Urdampilleta, Juan Domingo (2007)
Four South American species of Paullinia (P. elegans, P. meliaefolia, P. pinnata, and P. rhomboidea) were compared using conventional chromosome staining, C-Giemsa and C-chromomycin A3/4′,6-diamidino-2-phenylindole (C-CMA3/DAPI) banding, and fluorescence in situ hybridization (FISH) with a 45S ribosomal DNA (rDNA) probe. All species showed a somatic complement of 2n = 24 chromosomes, agreeing with earlier records in some cases, and showing a tendency for the chromosome number to be conserved in this genus. The chromosome number of P. rhomboidea is a new report. The karyotypes differed in chromosome size and degree of karyotype asymmetry. The chromosomal band patterns and location of the 45S rDNA sites are reported for the first time in the genus. Terminal C-CMA3 bands were associated with the 45S rDNA sites, but varied in number and size between the species. The occurrence of other C-Giemsa bands that were not revealed by CMA3 suggests that more than one family of repetitive DNA may be involved in karyotype differentiation. The systematic implications of these results on the infrageneric relationships are discussed.